The Glorious Deeds of Purna. A translation and study of the Purnavadana. Joel Tatelman. - Hahn, Michael (Buddhist Studies Review, 2003)
The Glorious Deeds of Purna. A translation and study of the Purnavadana. Joel Tatelman. Curzon, Richmond 2000, £40.00; Motilal Banarsidass, Delhi 2001. xii, 228 pp. Rs 295.00. ISBN 0-7007-1082-5.